Y2O3 nanoparticles decorated IN738LC superalloy manufactured by laser powder bed fusion: Cracking inhibition, microstructures and mechanical properties. (1st February 2022) - Guo, Chuan; Yu, Zhengrong; Hu, Xiaogang; Li, Gan; Zhou, Fan; Xu, Zhen; Han, Shuang; Zhou, Yang; Ward, R. Mark; Zhu, Qiang
Abstract: In-situ Y2 O3 nanoparticles decorated Inconel 738 LC composite by powder mixture is fabricated using laser powder bed fusion with different scan speeds and laser powers. The process window is significantly enlarged with the addition of 0.05 wt% Y2 O3 by removing the cracks in the as-printed parts. Well-dispersed Y4 Al2 O9 particles are formed during the reaction between the mixed powders and the laser beam. Obvious enrichment of Zr in the Y4 Al2 O9 particles by substitution for the yttrium is observed, which effectively eliminates the segregation of Zr along the grain boundaries. In this case, the cracks are mitigated since the formation of liquid film is correspondingly hindered at the last stage of solidification. In addition, the gains are coarsened to nearly double the size with the incorporation of Y2 O3 nanoparticles before and after heat treatment. As a result, the Y2 O3 -inoculated Inconel 738 LC exhibits an improved strength at 850 °C. Highlights: The crack is mitigated in IN738LC by the addition of Y2 O3 during LPBF. The added Y2 O3 reacts with Al to form well-dispersed Y4 Al2 O9 particles. Y4 Al2 O9 particles absorb Zr and hinder its segregation along grain boundaries. Y2 O3 addition induces coarser grains due to the low cooling rate caused by Y4 Al2 O9.